2022
DOI: 10.1007/s11051-022-05621-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polymer protected Pd–Ag/ZnO catalysts for phenylacetylene hydrogenation

Abstract: A simple and environmentally friendly method, based on sequential adsorption of polyacrylamide (PAM) and transition metal ions (Pd 2+ , Ag + ) on zinc oxide precipitated from water solution, was used to synthesize supported mono-and bimetallic catalysts with various Pd:Ag ratios. The catalyst characterization results indicated that PAM and metal ions are completely adsorbed by zinc oxide, forming polymer-stabilized Pd and Ag nanoparticles of 1-3 nm in size, evenly distributed on the support surface. The cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…In our prior studies [53,56] have been shown that interaction of polymers with metal ions on a support surface led to formation smaller active phase nanoparticles (~2 nm) to compare with those in similar unmodified supported catalysts. The transmission electron microscopy (TEM) image of Pd-HEC/ZnO catalyst showed the formation of finely dispersed palladium nanoparticles of ~2 nm evenly distributed on the surface of zinc oxide modified with HEC (Figure 3).…”
Section: Characterization Of Catalystsmentioning
confidence: 97%
See 2 more Smart Citations
“…In our prior studies [53,56] have been shown that interaction of polymers with metal ions on a support surface led to formation smaller active phase nanoparticles (~2 nm) to compare with those in similar unmodified supported catalysts. The transmission electron microscopy (TEM) image of Pd-HEC/ZnO catalyst showed the formation of finely dispersed palladium nanoparticles of ~2 nm evenly distributed on the surface of zinc oxide modified with HEC (Figure 3).…”
Section: Characterization Of Catalystsmentioning
confidence: 97%
“…The nanocatalyst was prepared by adsorption method, according to procedure described in [53,56]. А 5 mL water solution of 0.9×10 -2 M 2-hydroxyethylcellulose (HEC, 0.0192 g in 5 mL of water) was added dropwise to the aqueous suspension of inorganic sorbent (1 g ZnO in 15 mL of water) and stirred for 2 hours.…”
Section: Synthesis Of Pd-hec/zno Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experimental results on PA hydrogenation on PdAg alloys show that the catalysts exhibit excellent selectivity towards the production of styrene. At low conversion, the selectivity on Pd and PdAg are similar, but the selectivity on Pd tends drop at high conversion, while PdAg remains highly selective even at high conversion of PA. 8,9,43,44,64 The Pd:Ag ratio in the experimental systems is relatively high and it is reasonable to ask, whether ensembles of Pd-atoms on the surface, such as dimers or trimers, play a role in the hydrogenation process. While the surface of PdAg alloys tends to be terminated by Ag atoms, spectroscopy measurements on adsorbed CO on PdAg surfaces have shown that the formation of isolated Pd-sites on a surface take place only on low Pd surface coverage, typically below 0.002 monolayer.…”
Section: Selectivity Of Phenylacetylene Hydrogenationmentioning
confidence: 99%
“…10,12,41,42 PA hydrogenation on Pd and PdAg alloy catalysts reveals an interesting trend that, while neat Pd demonstrates reasonably high selectivity in PA hydrogenation, alloying Pd with Ag even enhances the selectivity at high conversion. 43,44 However, the Pd-to-Ag ratio in the PdAg alloys tends to be high, which prompts the question of whether active sites are composed of isolated Pd atoms, as occasionally asserted, or if they rather consist of Pd ensembles.…”
Section: Introductionmentioning
confidence: 99%